(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2022)
How can social work courses prepare students to be scholars of social movements, and also to act in solidarity with movements for social justice? How can graduate programs reimagine the professional socialization of social work students from aspiring for expertise toward a stance of life-long learning? How can instructors more deeply leverage our teaching practice to advance justice in our communities? This paper traces one attempt to answer these questions through a three-quarter graduate social work course designed to deepen students’ skills and knowledge in practices for social transformation, while amplifying existing social justice movements. Drawing on reflections from the instructor and five students, course artifacts, and insights from other students and community partners, this case study offers a model of community-engaged teaching that centers solidarity, reciprocity, and justice.